2012
DOI: 10.1097/sla.0b013e3182583e2e
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-Assisted Versus Open Distal Gastrectomy for Early Gastric Cancer

Abstract: LADG may be a technically feasible alternative for EGC when it is performed in experienced surgical centers in which patients undergoing LADG may benefit from the faster postoperative recovery. However, the currently available evidence cannot exclude the potential clinical benefits or harms, especially in the node-positive cases. Methodologically high-quality comparative studies are needed for further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0
27

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(156 citation statements)
references
References 41 publications
3
126
0
27
Order By: Relevance
“…Proponents of robotic technology, in particular, cite greater technical precision, more degrees of freedom in instrument articulation, and better visualization of anatomy relative to other surgical approaches [10]. With most of the experience and literature regarding surgery for gastric cancer coming from the East, previously published studies show a greater quantity of lymph nodes harvested during minimally invasive surgery, yet there is a general lack of consensus regarding improved R0 resection rates on the basis of the approach alone [11,[19][20][21][22][23]. For example, Vinuela et al [24] performed a meta-analysis of all English-language studies since 1992, including several from Eastern centers, and found that when they compared open versus laparoscopic distal gastrectomy outcomes, the former were associated with better lymph node harvest quantitatively, but no difference was seen in the odds of having less than the recommended minimum of lymph nodes on the basis of the approach alone.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of robotic technology, in particular, cite greater technical precision, more degrees of freedom in instrument articulation, and better visualization of anatomy relative to other surgical approaches [10]. With most of the experience and literature regarding surgery for gastric cancer coming from the East, previously published studies show a greater quantity of lymph nodes harvested during minimally invasive surgery, yet there is a general lack of consensus regarding improved R0 resection rates on the basis of the approach alone [11,[19][20][21][22][23]. For example, Vinuela et al [24] performed a meta-analysis of all English-language studies since 1992, including several from Eastern centers, and found that when they compared open versus laparoscopic distal gastrectomy outcomes, the former were associated with better lymph node harvest quantitatively, but no difference was seen in the odds of having less than the recommended minimum of lymph nodes on the basis of the approach alone.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of laparoscopy-assisted distal gastrectomy (LADG) has been assessed in many studies [1][2][3]. A multicenter phase II study has demonstrated that LADG can be performed safely by surgeons with sufficient experience [4].…”
Section: Introductionmentioning
confidence: 99%
“…В 2012 г. опубликован метаанализ и систематический обзор 22 исследований, посвященных сравнению результатов открытой и лапароскопической дистальной субтотальной резекции желуд-ка при РРЖ, куда вошло почти 3500 наблюдений [51]. Анализ по-казал, что лапароскопические операции сопровождаются лучши-ми непосредственными результатами и не ухудшают прогноз.…”
Section: выбор объема операции при рржunclassified